Gamification as strategy to improve reading skills - Lindao Bernardino, Irene Karina (2022)
The technological advances of our times have aroused the interest of all people from an early age and have turned them into digital natives. Currently teachers are taking advantage of this new trend of including games in the classroom, adapting this motivating and playful strategy to the student’s learning process of learning at different rates and styles. Gamification as an active learning strategy (ALS) is a novel phenomenon applied within the educational field, it offers an integrating, motivating, interactive and stimulating student response system (SRS) that solves low academic performance through active individual and collaborative participation whole class gets involved to meet the established challenges and the common weal.